Impact of Emotional Intelligence and Resilience on Salespersons’ Propensity to Leave - Soheila Heidari; Fakhraddin Maroofi; Arman Ahmadizad (کاوش‌های مدیریت بازرگانی, 2017)
This study aims to investigate the effects of emotional intelligence and resilience on salespersons’ propensity to leave, considering the mediating roles of emotional exhaustion and work-family conflict. The present paper is a questionnaire-based survey of sales forces in fifty eight firms in Kermanshah food industry. Overall, 215 salespeople were selected via Cochran’s formula and simple random sampling. The data were collected using a questionnaire whose validity and reliability were evaluated using construct and content validity indices and Cronbach’s alpha respectively. To analyze the data, descriptive statistics and structural equation modeling (SEM) were applied. The findings show that sales force propensity to leave, either directly or indirectly (via exhaustion and work-family conflicts), is significantly and negatively affected by their emotional intelligence, but direct effects are greater than indirect ones. Also, sales force propensity to leave, either directly or indirectly (via emotional exhaustion) is significantly and negatively affected by their emotional intelligence, but direct effects are greater than indirect ones. The results also indicate that work-family conflict has a positive and significant effect on sales forces’ emotional exhaustion, and emotional exhaustion has a positive and significant effect on the willingness of those forces to leave their organizations.